Evaluating resistances to health promotion campaigns with Discourse Analysis - De Melo e Costa, Stéphanie Lyanie; Alves, Wedencley (Revista Española de Comunicación en Salud, 2019)
Introduction: This paper argues the role of Discourse Analysis - DA (Michel Pêcheux, Eni Orlandi) as a theoretical-methodological contribution to the evaluation of health campaigns. Objectives: It shows how DA can be applied to identify and understand discourses of resistance to health promotion campaigns. Methodology: It analyses the HIV prevention campaign of the Brazilian Ministry of Health designed for the carnival of 2010, as well as individual interviews with two people living with HIV. Results: By comparing the discourses mapped in the campaign and those present in the interviews, some dissonance of senses, understood as forms of resistance, are identified. Discussion: Such results also lead to the discussion regarding biopower issues (Michel Foucault) and the relationship between power and resistance in historical processes of subjectivation. Conclusion: It is concluded that, before trying with campaigns to change individual’s practices towards behaviors that promote health, institutional practices must be changed in order to prioritize listening to people when designing such campaigns, by applying Discourse Analysis’s theoretical-methodological contributions.